Identifying Factors Affecting the Relationship between Department and Graduation Level of Informatics Engineering Students using Apriori Algorithm: A Case Study at Pamulang University - Thoyyibah T (LPPM Universitas Islam 45 Bekasi, 2023)
To cultivate the next generation of leaders, it is essential for teenagers to receive a high level of education. Typically, this education is acquired through attending lectures that produce a high GPA, which is considered a valuable achievement for students. The level of graduation achieved within the appropriate timeframe can also impact campus accreditation, especially for engineering students, particularly those pursuing informatics engineering. To improve graduation rates, it is necessary to use data mining to identify patterns and trends among graduating students. The a priori algorithm was used in this study to analyze school majors, the length of study, and student graduation rates. Through this algorithm, it was possible to identify one or more rules that can be used as benchmarks for predicting graduation rates. Based on the results and discussions of 30 students, the most effective rule for predicting graduation is a combination of the student's previous school major, a study period of 4 years or less, a GPA of 2.51-3.00, and passing all courses on time. Using the a priori algorithm, the rule was found to have a confidence value of 16 and a support value of 71.4%. This indicates that the rule is a reliable predictor of student graduation rates.